Porous ceramic nanofibers as new catalysts toward heterogeneous reactions. (October 2019) - Li, Zhihui; Liu, Suting; Song, Shugui; Xu, Wanlin; Sun, Yueming; Dai, Yunqian
Abstract: The advent of porous ceramic nanofibers offers tremendous opportunities for new applications in heterogeneous catalysis, due to their intrinsic features such as high surface area, tunable compositions and extraordinary stability. This paper provides a brief review of current research activities that focus on the fabrication of porous ceramic nanofibers by electrospinning, as well as their applications in heterogeneous catalytic reactions. We begin with a brief introduction of electrospinning in the context of ceramic nanofibers, and then discuss the approaches of the functionalization of nanofibers with a porous structure. Afterward, we continue with a highlight of some recent applications of porous ceramic nanofibers, with a focus on the physiochemical properties of porous ceramic nanofibers as well as their applications in heterogeneous catalysis towards energy and environmental aspects. At the end, we conclude this review with some perspectives on the challenges, opportunities, and new directions for their future development. Graphical abstract: This paper provides a brief review of current research activities that focus on the fabrication of porous ceramic nanofibers by electrospinning, as well as their applications in heterogeneous catalytic reactions.Image 1 Highlights: Recent progresses in the fabrication of ceramic nanofibers are reported. Approaches to the functionalization of nanoﬁbers with a porous structure and catalytical nanoparticles are summarized. Applications of ceramic nanoﬁbers as novel catalysts toward important heterogeneous reactions are discussed. Perspectives on the challenges and opportunities for future development of ceramic nanofibers as catalysts are concluded.